(untitled) (Scientific journal of the Fergana State University, 2024)
The article discusses the need and importance of environmental education for students of higher educational institutions, the essence of environmental education, the dictionary meaning of the term “mechanism”, the development of mechanisms for the implementation of environmental education in the areas of higher pedagogical education and discussed its developments, the results of experimental work are described in detail.